The Role of the Marine and Fisheries Office of Labuhanbatu Regency Towards the Protection of the Terubuk Fish (Tenualosa ilisha) - Muhammad Rufli Zendri Batubara; Sriono Sriono; Kusno Kusno (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
This study aims to determine the role of the Department of Marine Affairs and Fisheries in Labuhanbatu Regency in protecting the terubuk fish (Tenualosa ilisha). This type of research is an empirical research with a qualitative approach with the techniques used in data collection, namely: interviews and observations. The results showed that the role of the Department of Marine Affairs and Fisheries in Labuhanbatu Regency had been carried out well, namely in maintaining the population of terubuk fish and proposing regulations in the form of Decree of the Minister of Maritime Affairs and Fisheries Number 43 of 2016 concerning Protection of Terubuk Fish (Tenualosa ilisha). The inhibiting factors are:the attitude of the fishing community's behavior that does not care about the threat of the worst fish from extinction when caught on a forbidden dayand the lack of knowledge of the fishing community on the protection of the terubuk fish species (Tenualosa ilisha). Meanwhile, efforts to overcome this are by socializing, coaching and monitoringon an ongoing basis so that it is important to obey the regulations that have been set and must be truly understood by the community, especially the coastal fishermen of the Barumun River watershed.